2011
DOI: 10.1148/radiol.11102136
|View full text |Cite
|
Sign up to set email alerts
|

Localized Scleroderma: MR Findings and Clinical Features

Abstract: MR imaging reveals musculoskeletal involvement in patients with localized scleroderma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 25 publications
1
38
0
5
Order By: Relevance
“…A review of MRI findings of LS has shown that fascial thickening and enhancement were notable in addition to subcutaneous septal thickening [13]. In our case, contractured fasciae at the posteromedial side of the thigh could distort the fractured femur as if a strained string had bent a bow.…”
Section: Discussionmentioning
confidence: 69%
“…A review of MRI findings of LS has shown that fascial thickening and enhancement were notable in addition to subcutaneous septal thickening [13]. In our case, contractured fasciae at the posteromedial side of the thigh could distort the fractured femur as if a strained string had bent a bow.…”
Section: Discussionmentioning
confidence: 69%
“…Due to its depth of penetration, which is a function of frequency, the usefulness of ultrasonography is somewhat limited to the skin and subcutaneous tissue. In this regard MRI is more advantageous and allows for better assessment of deeper structures such as the fascia and underlying muscle [45, 46]. As with ultrasonography, MRI can be resourceful in monitoring disease activity and response to treatment [47].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study reported MRI findings in 43 morphea patients; MRI enabled confirmation of musculoskeletal abnormalities in all but one of the patients in whom musculoskeletal involvement was clinically suspected [131]. A recent retrospective study confirmed the potential of MRI in detection of musculoskeletal involvement [132].…”
Section: Assessment Of Musculoskeletal Involvementmentioning
confidence: 99%